Evolving Policy Measures for Promoting Agricultural Education in Tertiary Institution in North-Eastern Nigeria to Reduce Youth Restiveness - J. A, Ukonze; J. C., Onuoha (Journal of Home Economics Research, 2024)
The study was carried out to find out how policies for promoting Agricultural education in tertiary institutions can help in reducing youth restiveness in North-eastern Nigeria. The sample size for the study was 52 directors from the ministry of education and 88 extension agents. A structured questionnaire was used for collecting data from the respondents and the data collected were analyzed using weighted mean to answer the research questions and t-test to test the hypotheses at 0.05 level of significant. It was found out that all the items identified were government policy measures that promote agricultural education towards reducing youth restiveness. It was therefore recommended that the four measures identified in this study be considered by government as guidelines for reducing youth restiveness in tertiary institution in North Eastern Nigeria.